2012
DOI: 10.1007/s00198-012-1955-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morning vs. evening teriparatide injection on bone mineral density and bone turnover markers in postmenopausal osteoporosis

Abstract: 12-month morning administration of TPTD resulted in a larger increase in the lumbar spine BMD than the evening application. The timing of TPTD administration may be important for its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
1
17
1
1
Order By: Relevance
“…While PTH agents are widely used for osteoporosis, it has been reported that they enhance the early chondrogenic stages of endochondral bone formation 27 . A previous study on the effects of teriparatide administration in osteoporosis patients reported twice the increase in bone mineral density following a morning administration compared to an evening administration 28 , and our data (this study and our previous study 19 ) suggest that PTH directly changes the bone and cartilage circadian clock state. These indicate the possibility that circadian clock directly modulates PTH function of bone mineral density increase.…”
Section: Discussionsupporting
confidence: 75%
“…While PTH agents are widely used for osteoporosis, it has been reported that they enhance the early chondrogenic stages of endochondral bone formation 27 . A previous study on the effects of teriparatide administration in osteoporosis patients reported twice the increase in bone mineral density following a morning administration compared to an evening administration 28 , and our data (this study and our previous study 19 ) suggest that PTH directly changes the bone and cartilage circadian clock state. These indicate the possibility that circadian clock directly modulates PTH function of bone mineral density increase.…”
Section: Discussionsupporting
confidence: 75%
“…In an investigation using DXA, Neer et al ([2001]) reported that a 40-µg dose of teriparatide decreased bone mineral density at the shaft of the radius by two more percentage points. Michalska et al ([2012]) investigated the efficacy of daily teriparatide at the distal 1/3 radius using DXA and reported a significant decrease in BMD of 2–3% at 6 months. Using the results of hr-pQCT, Macdonald et al ([2011]) reported that BMD of the distal radius decreased with daily teriparatide.…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatide (recombinant human PTH (1-34)) is a bone anabolic agent for treatment of patients with osteoporosis ( Augustine and Horwitz 2013 ). In osteoporosis patients, morning teriparatide treatment appears to function better than night-time administration, but the detailed biological mechanism is not fully understood ( Michalska et al 2012 ).…”
mentioning
confidence: 99%